Phyto-Inspired Design: Innovative Solutions for Architecture - Srisuwan, Touchaphong (International Journal of Building, Urban, Interior and Landscape Technology, 2020)
For a long time, designers have mainly taken inspiration from nature as a solution, defined as bio-inspired, to overcome design problems. Phyto-inspired approaches, or phytomimetics, is a subdivision of bio-inspired approaches, which focus on inspiration taken from plants with regard to materials, structures, and movements, for example. Many well-known buildings and inventions in various time periods were designed by using phytomimetic approaches based on available technologies, such as the Gothic-style fan vault in medieval churches, many works with dendriform structures designed by Gaudi, coiled extension wires, and the development of monoplane aircraft in the twentieth century. This article intends to explore the use of plant-inspired problem-solving approaches in architectural design by subdividing them into three main types of inspirations: phytomorphism, dendriform structures, and phytomechanisms. Several case studies are presented to show how architects and designers can use inspiration from plants as a potential solution for sustainable and efficient design.